Changing Concepts in Reattachment of Tooth Fracture (Update Dental College Journal, 2013)
The majority of dental trauma involves anterior teeth, especially the maxillary central incisors. A crown fracture with pulp tissue involvement, severe sensitivity, and pain is certainly unpleasant for the patient. If the original tooth fragment is retained following fracture, the natural tooth structures can be reattached using adhesive protocols to ensure reliable strength, durability and aesthetics. This case report will discuss a case history of 21 year old patient who accidentally injured his maxillary left central incisor. After local anesthesia, the fractured part was carefully separated and at the same time, the Supernumerary tooth was removed. After completion of root canal treatment, the tooth fragment was successfully reattached with an adhesive tooth reattachment technique. DOI: http://dx.doi.org/10.3329/updcj.v2i2.15535 Update Dent. Coll. j: 2012; 2 (2): 42-46